The lightning thief - Riordan, Rick (Riordan, Rick. Percy Jackson & the Olympians, 2006)
After learning that he is the son of a mortal woman and Poseidon, god of the sea, twelve-year-old Percy is sent to a summer camp for demigods like himself, and joins his new friends on a quest to prevent a war between the gods.